Análisis de la propagación de una señal MMWAVE en entornos INDOOR (2016)
The effect of transmission, reflection and diffraction on the path loss of a signal in the 38 GHz band in indoor using Wireless InSite is studied. The results are shown in figures because their behavior did no let an accurate modeling to be possible. Likewise, the path loss estimated from the results in an office and mall scenarios was found to be reliable compared to the path loss obtained from simulation. The contribution of this study is the analysis and loss values due to the three physical phenomenon that allow planning indoor mmWave band systems which will be a foundation technology of the Fifth Generation (5G) of mobile systems.